Identifikasi Penyakit Lambung Menggunakan Metode Case Based Reasoning Berbasis WEB - Surya Aulia Rahman. S; Ayu Prima Siska; Mardhotillah Mardhotillah (International Forum of Researchers and Lecturers, 2026)
Gastric disease is a disease that cannot be taken lightly, because if it is allowed to continue it can cause other diseases to appear and can also cause death if not treated immediately. Stomach disease can be caused by an inappropriate diet, a burden on the mind and also an infection caused by bacteria. Given these problems, this study can only provide a diagnosis of gastric disease, namely gastritis, stomach ulcers, GERD, gastric cancer. The symptoms given to the system are based on common symptoms. This study aims to create an expert system for diagnosing gastric disease using the Case Based Relational (CBR) method. Based on the testing and analysis of an expert system for diagnosing gastric disease using a Web-based Case Based Reasoning (CBR), it is capable of diagnosing 5 gastric diseases Gastritis, gastric ulcer, GERD, gastric cancer by calculating the similarity value with the Case Based Reationing (CBR) method.